Do informative value and entertainment value in tiktok influence purchase decision on somethinc products - Marisca, Tirza Eudia; Azazi, Anwar; Purmono, Bintoro Bagus; Fauzan, Rizky; Yakin, Ikram (Institute of Computer Science (IOCS), 2023)
The development of the digital era has an impact on many areas, including product marketing. One way to market products in the digital era is to use social media as a marketing method to promote products. The high social media use by the general public is an excellent opportunity for business people to expand their market reach. And without any restrictions. One of the products widely promoted via social media is beauty products, which are currently increasingly competitive. Therefore, the right product marketing strategy must be implemented to attract consumer attention through social media. This research aims to determine the impact of informative value, entertainment value, and trust in brand posts on purchase decisions for Somethinc products. The questionnaire used in the data collection process had 225 participants. The sampling technique used was purposive sampling using Structural Equation Modeling (SEM) and AMOS statistical tools. These findings show that informative value and entertainment value have a positive and significant influence on trust in brand posts, and trust in brand posts also has a positive and significant influence on purchase decisions. Trust in brand posts mediates between informative value and entertainment value and purchase decisions